A mathematical equation solving system using accelerometer sensor - Shrivastava D.; Sinha R.; Saraswat S.; Gupta H.P.; Dutta T. (My University, 2025)
This paper presents a system that continuously recognizing the operands and operator in a mathematical equation, solve the equation using accelerometer sensor, and share the information to the students. The system creates a labeled database for recognizing the correct operands, operator, and starting and ending points of the equation. The system uses machine learning technique for recognizing and solving the equation using the created dataset. In addition, a prototype system is developed and adequately tested on real user data. The prototype uses an accelerometer sensor for extracting the equation writing activities. The system uses Bluetooth Low Energy (BLE) for wirelessly transferring the sensed data of equation writing activities to the students. The system is suitable for teacher-student smart interaction due to its low cost, small size, and low-power consumption. Prototype results illustrate that the system provides the desired quality of accuracy. © 2018 IEEE.